Kajian Terhadap Isu Hubungan Kontraktor Utama Dengan Subkontraktor Berkaitan Aspek Pengurusan Risiko Projek Pembinaan - Sy Md Zairrul Azmy, Syed Farizuan Amir; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2021)
The issue of the relationship of the main contractor with the subcontractor related to the risk management aspects of the construction project should be taken seriously as it can disrupt the smooth construction process of the project. Failure to cooperate between the two parties can trigger various risks in construction projects such as collapse and defects in the construction structure. The objective of this study is to identify the factors that lead to relationship problems between the main contractor and subcontractor from the aspect of construction project risk management and suggest measures to improve the relationship of major contractors and subcontractors to reduce risk in construction project management. The study data was obtained through a questionnaire distributed to the respondents, namely Grade 7 (G7) contractors throughout the district of Johor Bharu, Johor. Literature review and distribution of questionnaires were used to achieve the objectives of the study. Quantitative methods have been used in this study where the information obtained will be analyzed through mathematical and statistical analysis as stated in numbers, graphs, and tables. Questionnaire forms are distributed to respondents virtually or (google form) via email, WhatsApp, and Facebook. The data obtained will be analyzed using the frequency analysis method (Frequency Analysis), and the descriptive analysis method using Statistical Package for Social Sciences (SPSS) version 20. Based on the results from the first objective of the study shows that the main factor that causes problems is subcontractors not performing Construction work according to the specifications set by the contractor with the highest mean value. Based on the findings of the second objective, it shows that the majority of respondents gave a statement agreeing to the measures where subcontractors need to ensure construction work according to the specifications directed by the contractor. Therefore, contractors and subcontractors need to be professional and play a good role to ensure construction projects run smoothly